2011
DOI: 10.1016/j.pepi.2010.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of variable uncertainties in seismic tomography models on constraining mantle viscosity from geoid observations

Abstract: . (2011) AbstractThe radial viscosity structure of the Earth is explored on the basis of the geoid observations. The variations of uncertainty in seismic tomography models are accounted for when finding the radial viscosity structure. The new methodology we propose attempts to fit more closely those features of the geoid that are better constrained by tomography models and avoids to fit those features that are poorly constrained. This approach is particularly important because the error of geoid predictions c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 41 publications
(47 reference statements)
1
12
0
Order By: Relevance
“…Their downwellings widened with depth and then ponded ∼300 km beneath the top of the asthenosphere. Their viscosity increased by a factor of 37 over that interval to approximately 10 20 Pa s, consistent with the results of Lee et al [2011] and Harig et al [2010]. From the model heat flow in equilibrium with thin lithosphere in the model of van Wijk et al [2010] is about 2.5 times that in my models, so the anomaly from is 2.5 times mine, 1750 K km.…”
Section: Downwelling Materials Thicknesssupporting
confidence: 84%
See 2 more Smart Citations
“…Their downwellings widened with depth and then ponded ∼300 km beneath the top of the asthenosphere. Their viscosity increased by a factor of 37 over that interval to approximately 10 20 Pa s, consistent with the results of Lee et al [2011] and Harig et al [2010]. From the model heat flow in equilibrium with thin lithosphere in the model of van Wijk et al [2010] is about 2.5 times that in my models, so the anomaly from is 2.5 times mine, 1750 K km.…”
Section: Downwelling Materials Thicknesssupporting
confidence: 84%
“…I use joint inversions of tomography and geoid data. Global inversion yields ∼10 20 Pa s at mid‐depths in the upper mantle [e.g., Lee et al , 2011]. Analysis of geoid anomalies on the leading and trialing continental margins of Australia yields this viscosity for the asthenosphere and 10 to 100 times this viscosity for the transition zone [ Harig et al , 2010].…”
Section: Downwelling Materials Thicknessmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncertainties of the seismic tomographic models would be expected to influence the parameters recovered in inversions (Lee et al, 2011). However, all the seismic tomography models tested by Lee et al (2011) yield a low viscosity transition zone compared to the upper mantle. The five layer viscosity inversions yield a low viscosity asthenosphere (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Panasyuk and Hager (2000a) have found this feature employing a whole-mantle convection model. On the other hand, Lee et al (2011) have demonstrated that it disappears if one considers the variable uncertainties of tomography models. Therefore, (Gu et al, 2003) including the TZ boundaries; (dashed) for the previous S20a model (Ekström and Dziewonski, 1998).…”
Section: Viscositymentioning
confidence: 99%